2021
DOI: 10.1109/access.2021.3074897
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of Road Types From the Third Military Mapping Survey of Austria-Hungary Historical Map Series With Deep Convolutional Neural Networks

Abstract: With the increased amount of digitized historical documents, information extraction from them gains pace. Historical maps contain valuable information about historical, geographical and economic aspects of an era. Retrieving information from historical maps is more challenging than processing modern maps due to lower image quality, degradation of documents and the massive amount of non-annotated digital map archives. Convolutional Neural Networks (CNN) solved many image processing challenges with great success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Can et al [9] identified seven different road types from the Generalkarte historical map series using CNN-based classifiers, with an IoU value of around 0.45 and a pixel-wise accuracy of 0.93. In general, the precision values of different road types were lower than the recall values.…”
Section: Data 21 Data Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Can et al [9] identified seven different road types from the Generalkarte historical map series using CNN-based classifiers, with an IoU value of around 0.45 and a pixel-wise accuracy of 0.93. In general, the precision values of different road types were lower than the recall values.…”
Section: Data 21 Data Descriptionmentioning
confidence: 99%
“…Manual digitization has still been widely used for reliable labeled data preparation for use in the learning process of artificial intelligence-based approaches. It took Vectorization of historical maps and aerial photographs has been conducted mainly through the on-screen digitization technique, which is time-consuming and labor-intensive [4,8,9]. Manual digitization has still been widely used for reliable labeled data preparation for use in the learning process of artificial intelligence-based approaches.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such recent efforts include the mining of (historical) map collections by their content or associated metadata [32][33][34][35][36][37], automated georeferencing [18,[38][39][40] and alignment [41,42], text detection and recognition [43][44][45], or the extraction of thematic map content, often involving (deep) machine learning methods, focusing on specific geographic features such as forest [46], railroads [33,47], road network intersections [48,49] and road types [50], archeological content [51] and mining features [52], cadastral parcels boundaries [53,54], wetlands and other hydrographic features [55,56], linear features in general [57], land cover / land use [58], urban street networks and city blocks [34], building footprints [13,59,60] and historical human settlement patterns [61][62][63]. Other approaches use deep learning based computer vision for generic segmentation of historical maps [64,65], generative machine learning approaches for map style transfer [66,67] or attempt to mimic historical overhead imagery based on historical maps [68].…”
Section: Introductionmentioning
confidence: 99%